Profissão, tempo, relações: tensões de gestores de instituições de ensino superior na contemporaneidade - Ramirez, Rosa Eulógia (Universidade do Vale do Rio dos Sinos, 2016)
This doctoral thesis is aimed at investigating the tensions that take part in the daily lives of teachers/researchers in charge of management positions in higher education institutions which are, from the perspective of this research, institutional, temporal and relational tensions. It also seeks to analyze the implications in daily lives of managers from Public Institutions, Private Confessional, Community Private, and Private ones and to understand the sources of these tensions. The research is based on theoretical perspectives in management as a social practice, leadership and identity, which contributes to reflect about issues regarded to training and experience of these individuals in their integral dimension. From the perspective of Depth Hermeneutics proposed by Thompson (2011), in the course of the chapters it is discussed the themes seeking to respond to the anxieties: which are the tensions that take part in daily lives of those who take the lead in management positions in higher education institutions of different kinds? What are the implications such tensions generate in their professional and personal lives? The methodological approach is anchored in Depth Hermeneutics involving documentary and bibliographical studies, complemented by qualitative analysis of data collected by four in-depth interviews with leaders of Public Higher Education Institutions, Private Confessional, Community Private and Private ones. From the dialogue with those university managers, the interpretation and reinterpretation of the data in the light of the references and the three macro analysis categories, it was found seven dimensions of tensions which were more visible during the interviews: institutional tensions arising from the accumulation of responsibilities, from the process of the managers’ development and training, from the decision-making process, and from the pursuit of excellence; temporal tensions arising from the transience of management positions and lack of time; relational tensions and their implications to the relational and family dimensions arising from the overlap of professional life upon their personal life. The data also make clear that such dimensions as well as the tensions in general are deeply interrelated and they impact profoundly the routine and the lives of university managers.
Keywords: Tensões; Gestores universitários; Identidade; Ensino superior; Tensions; University managers; Identity; Higher education; ACCNPQ::Ciências Humanas::Sociologia